Evaluation and Performance Analysis of Liquefied Petroleum Gas Cylinders - Fadel, Abdulnnaser H.; Abdullrhman, Musa M.; Elsagisli, Mohamed Y. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
This paper presents the experimental results of the tensile, bending, hardness, hydrostatic testing, and microstructural properties of liquefied petroleum gas cylinders from local sources. The burst pressure and fracture sites were also investigated. In addition, know how LPG cylinders are compliant with ISO 4706 requirements as per standard to get approval and acceptance. The tests were performed on three samples (C1, C2, and C3), and all the tests were according to the specification. Tensile testing was carried out at room temperature (23C°) as per ISO 6892-2016. Tensile test specimens with a gauge length of 50 mm were prepared from the sidewall of cylinders. The equipment used is built up around a 250 KN maximum capacity of (Instron Servo-Hydraulic Testing Machine Model 1332). At the same time, micro-hardness testing was carried out as per ASTM A384. Diamond indenter (pyramid) with a face angle of 136° was used. During testing (1kg) load was applied on the sample with a dwell time of 15 seconds. As for bending tests were carried out in accordance with ISO 7438 for all cylinders to evaluate their welding qualities. The results of microstructural characterization show that the carbon content for all samples averaged 0.067 wt.% and manganese 0.46 wt.% and the microstructure was largely ferritic. The tensile strength of the parent metal showed that LPG gas cylinders recorded high tensile strength of 418 MPa on average, yield strength of 291 MPa on average, a % elongation 26.6 (for parent metal), the tensile strength of 449 MPa as average, yield strength of 314 MPa as average, % elongation 32 (for weld metal) and hardness of 143 (kg/mm2) as average by Vickers scale. Moreover, in the hydrostatic pressure test, the computer controlled electro-hydraulic servo pressure test machine was used. The results of the hydrostatic pressure test were as follows, pressure burst (BP) 103 bar, nominal hoop stress 528 MPa, volumetric expansion 25%, hydrostatic extend ratio 3.9%, sites of failure exist out of welding, and finally no fragmentation observed regarding to fracture types. All samples tested exhibited high resilience to crack propagation which showed ductile fracture after burst and tensile tests.